2020
DOI: 10.3390/ma13071764
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Porous Structure on the Microwave Absorption Capacity of Soft Magnetic Connecting Network Ni/Al2O3/Ni Film

Abstract: Microwave radar absorbing materials have been the focus of the radar stealth research field. In this study, ceramic structured porous honeycomb-like Al2O3 film was prepared by anodic oxidation, and an Ni layer was deposited on the Al2O3 film via electrodeposition in a neutral environment to form a flower- and grain-like structure in a three-dimensional (3D) network Ni/Al2O3/Ni film. The films both have a through-hole internal structure, soft magnetic properties, and absorb microwaves. The dielectric loss value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…Particularly for microwaves emitted from standard microwave ovens at a frequency of 2.45 GHz, the small pore size of CAC notably diminishes its microwave absorption efficiency. 41,42 It is recognized that microwave absorbers with mesoporous pores, ranging from 2 to 50 nm, are more aptly suited for the absorption of low-frequency microwaves. 43…”
Section: Resultsmentioning
confidence: 99%
“…Particularly for microwaves emitted from standard microwave ovens at a frequency of 2.45 GHz, the small pore size of CAC notably diminishes its microwave absorption efficiency. 41,42 It is recognized that microwave absorbers with mesoporous pores, ranging from 2 to 50 nm, are more aptly suited for the absorption of low-frequency microwaves. 43…”
Section: Resultsmentioning
confidence: 99%
“…To date, many metal oxides/sulfides, such as NiO, MnO 2 , TiO 2 , ZnO, Al 2 O 3 , Fe 3 O 4 , MoS 2 , and Ni 3 S 2 , have been employed in combination with Ni and Ni-containing alloys, and all the resultant composites have exhibited significant superiority in microwave absorption [90,[94][95][96][97][98][99][100][101][102][103][104][105][106]. For example, Wang et al obtained core-shell Ni@Ni 2 O 3 particles through the in situ oxidation of Ni particles in the presence of hydrogen peroxide, and they confirmed that the thin Ni 2 O 3 shell greatly improved the impedance matching of Ni@Ni 2 O 3 particles, but affected their relative complex permeability less [107].…”
Section: Ni-related Composites With Metal Oxides/sulfidesmentioning
confidence: 99%
“…Nowadays, various mainstream methods have been widely investigated with the fabrication of porous ceramics and composites: partial sintering, replica template, sacrificial template, and direct foaming [ 21 , 22 , 23 , 24 ]. However, the challenges to these methods, including the complex manufacturing processes and high sintering temperatures, as well as the simple methods to shape porous SiC ceramics into complex shapes, remain unexplored [ 25 ].…”
Section: Introductionmentioning
confidence: 99%